Theranostic quantum dots for crossing blood–brain barrier in vitro and providing therapy of HIV-associated encephalopathy - Yong, Ken-Tye (2014)
The blood–brain barrier (BBB) is a complex physiological checkpoint that restricts the free diffusion of circulating molecules from the blood into the central nervous system. Delivering of drugs and other active agents across the BBB is one of the major technical challenges faced by scientists and medical practitioners. Therefore, development of novel methodologies to address this challenge holds the key for both the diagnosis and treatment of brain diseases, such as HIV-associated encephalopathy. Bioconjugated quantum dots (QDs) are excellent fluorescent probes and nano-vectors, being designed to transverse across the BBB and visualize drug delivery inside the brain. This paper discusses the use of functionalized QDs for crossing the blood–brain barrier and treating brain disease. We highlight the guidelines for using in vitro BBB models for brain disease studies. The theranostic QDs offers a strategy to significantly improve the effective dosages of drugs to transverse across the BBB and orientate to the targets inside the brain.